Teachers’ Professional Development at Public Campuses in Nepal: Opportunities and Challenges - Panthee, Dinesh (KMC Research Journal, 2021)
Teachers’ professional development activity is an opportunity for teachers to share their knowledge and develop new instructional practices. It keeps academics up-todate with the changing world and knowledge. The objective of this study was to explore opportunities and challenges of teacher professional development in public campuses of Nepal. This study was qualitative approach with a phenomenological design. The participants of the study were three teachers of different public campuses of Rupendehi district selected purposively. The study revealed TPD opportunities for teachers of public Campuses deserve high significance in the sense that they help teachers develop various kinds of professional skills, knowledge, new techniques of teaching. However, Public campuses are facing many challenges which include proper management TPD for faculties of their campuses and there is a gap between policies and practices in implementation of TPD in public campuses of Nepal.